Elder adult's social participation in the community - Felly Yandi Jay-Daudinot (Universidad de Guantánamo, 2016)
This research is developed in the suburban community of Palmira, in the El Caribe District in Guantanamo City. The main objective is to propose a system of recreational physical activities to engage and extend social cooperation to as many people in the community, through this vital work where participants find a common inclusive space in interpersonal relationships; very necessary, to recover emotionally and physically, letting all participants make their own decisions which encourages social participation, taking into account their needs and psychosocial motivations.